2019
DOI: 10.1016/j.athoracsur.2018.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Regional Cerebral Perfusion and Cognition After Cardiac Operation

Abstract: Background. Cardiac operation has been associated with increased risk of postoperative cognitive decline, as well as dementia risk in the general population. Few studies, however, have examined the impact of coronary revascularization or valve replacement or repair operation on longitudinal cerebral perfusion changes or their association with cognitive function.Methods. We examined longitudinal changes in cerebral perfusion among 54 individuals with cardiac disease; 27 undergoing cardiac operation and 27 match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…When the damaged cognitive preservation was challenged by a cognitive task such as increasing working memory load, the degree centrality and local coherence in the left dorsal posterior cingulate cortex (dPCC) increased, which was inversely associated with global cognitive outcomes (42). It has also been demonstrated that cognitive function such as psychomotor speed would be improved after cerebral arterial perfusion increased (43). Based on previous and present results, we speculated that POCD patients might have subtle cognitive decline and functional connectivity alterations before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…When the damaged cognitive preservation was challenged by a cognitive task such as increasing working memory load, the degree centrality and local coherence in the left dorsal posterior cingulate cortex (dPCC) increased, which was inversely associated with global cognitive outcomes (42). It has also been demonstrated that cognitive function such as psychomotor speed would be improved after cerebral arterial perfusion increased (43). Based on previous and present results, we speculated that POCD patients might have subtle cognitive decline and functional connectivity alterations before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement could be driven by increased blood perfusion in the brain resultant of improved functional cardiac output following surgery. 44 Further, our follow-up sample may have been positively biased (more cognitively healthy), due to an increased withdrawal rate in those who experienced delirium. The current study investigated at a group level, comparing control with CCT participants.…”
Section: Deliriummentioning
confidence: 99%
“…This approach derived four factor scores that correspond to four cognitive domains: verbal memory; abstraction and visuospatial orientation; visual memory; and attention and concentration. Postoperative cognitive dysfunction was defined as a ≥ 1 standard deviation decrease in one or more of these four cognitive domain from baseline to 6 weeks after surgery as previously described [6,34,35,[37][38][39][40][41][42]. The 6-week time point was selected because it falls within the 1-12month window that POCD/neurocognitive disorder, postoperative occurs, and the 6-week time point has been previously been used extensively in prior studies [6,34,35,[37][38][39][40][41][42].…”
Section: Cognitive Testingmentioning
confidence: 99%